COMPARATIVE ANALYSIS OF ENDOTHELIAL FUNCTION AND ELASTICCHARACTERISTICS OF THE ARTERIES IN CHILDREN WITH JUVENILE IDIOPATHIC AND REACTIVE ARTHRITIS - V. L. Мarchuk; N. V. Sobotuyk (Вопросы современной педиатрии)
Aim: to estimate function of the endothelium and arterial elastic characteristics in children with various manifestations of juvenileidiopathic (JIA) and reactive arthritis (ReA) and possible use of studied indicators for early and differential diagnostics. Patients and methods: in cross sectional study we analyzed arterial stiffness (SIngl) and endothelial function of 36 patients with JIA, 32 — with ReA and 23 healthy children with help of the pulse contour analysis. Results: children with JIA had significantly higher SIngl values (p = 0,0095) than patients with ReA and healthy children. SIngl of children with JIA positively correlated with disease activity (rs = 0,33; p = 0,048) and did not depend on duration of disease (rs = 0,025; p = 0,89). Children with JIA had significantly lower endothelialdependent vasodilatation function in comparison with healthy children (p = 0,026), but not with patients with ReA (p = 0,598). Conclusions: arterial stiffness in children with JIA significantly differs from indicators of patients with ReA and healthy children already at early stages of the disease and can be used as additional diagnostic criterion.